2021
DOI: 10.1186/s12906-021-03296-0
|View full text |Cite
|
Sign up to set email alerts
|

Alisol A 24-acetate stimulates lipolysis in 3 T3-L1 adipocytes

Abstract: Background Alisol A 24-acetate (AA-24-a), one of the main active triterpenes isolated from the well-known medicinal plant Alisma orientale (Sam.) Juz., exhibits multiple biological activities including hypolipidemic activity. However, its effect on lipid metabolism in adipocytes remains unclear. The present study aimed to clarify the effect of AA-24-a on adipocyte lipolysis and to determine its potential mechanism of action using 3 T3-L1 cells. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Terpenoids comprise five-carbon isoprene units and have diverse effects on obesity and its associated metabolic diseases. Triterpenoids include 18β-glycyrrhetinic acid (18β-GA) ( 88 ), ursolic acid ( 89 ), acetyl-keto-β-boswellic acid (AKBA) ( 90 ), alisol A 24-acetate (AA-24-a) ( 91 ), celastrol ( 92 ), and betulinic acid ( 93 ). All of these reduce neutral lipids in the cytosol and increase FFA release.…”
Section: Natural Products Involved In Lipolysismentioning
confidence: 99%
“…Terpenoids comprise five-carbon isoprene units and have diverse effects on obesity and its associated metabolic diseases. Triterpenoids include 18β-glycyrrhetinic acid (18β-GA) ( 88 ), ursolic acid ( 89 ), acetyl-keto-β-boswellic acid (AKBA) ( 90 ), alisol A 24-acetate (AA-24-a) ( 91 ), celastrol ( 92 ), and betulinic acid ( 93 ). All of these reduce neutral lipids in the cytosol and increase FFA release.…”
Section: Natural Products Involved In Lipolysismentioning
confidence: 99%
“…The related compound, Ali-A 24-acetate, is also able to reduce liver lipid deposition in hyperlipidemic mice via a blockade of AMPK activation to promote glucose metabolism and by promoting expression of ATP binding cassette transporters ABCG1 and ABCA1 [ 60 , 61 ]. The compound stimulates lipolysis of adipocytes by activating protein kinase A (PKA)-mediated phosphorylation of hormone-sensitive lipase [ 62 ]. These observations make Ali-A 24-acetate and Ali-B 23-acetate good candidates for the treatment of nonalcoholic fatty liver disease and its comorbidities [ 63 ].…”
Section: Pharmacological Properties Of Alisolsmentioning
confidence: 99%
“…[Alismataceae]. AA-24-a can improve the abnormal accumulation of lipids in the liver by regulating a variety of molecular mechanisms, such as improving liver lipid deposition through ABCA1/ABCG1 pathway in Apoe−/− mice model ( 53 ), binding to HMG-COA reductase ( 54 ), activating PKA-mediated hormone-sensitive lipase phosphorylation and down-regulating perilipin A in vivo and in vitro ( 55 ). Alisol B 23-acetate (AB-23-a), a natural triterpenoid, can induce mobilization of internally stored calcium, leading to autophagy by activating the CAMKK-AMPK- pathway in vitro ( 56 ), to improve abnormal lipid metabolism and reduce cytotoxicity.…”
Section: Herbs and Active Tcm Ingredientsmentioning
confidence: 99%
“…UDCA treatment suppressed the activation of AKT, mTOR, and CRTC2 and the expression of nSREBP-1 in vitro ( 76 ). Additionally, it has been reported that UDCA administration promotes autophagy by activating the AMPK pathway to inhibit apoptosis ( 55 ).…”
Section: Herbs and Active Tcm Ingredientsmentioning
confidence: 99%